Analisis dalam Menguraikan dan Memproyeksikan Ragam Organisasi Publik di Indonesia - Rika Aprilliyanti; Eli Apud Saepudin; Surni Ernawati; M Afan; Ahmad Ripa’i; Ulpi Fitriani (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The purpose of the analysis is to describe and project the variety of public organizations in Indonesia to understand the dynamics of public organizations in Indonesia and can become a basis for formulating appropriate policies in managing organizations in the future. Public organizations are the largest organizations that accommodate all levels of society within the scope of the State and have legitimate (legitimized) authority in the fields of politics, government administration and law in an institutionalized manner so that they have the obligation to protect their citizens and serve their needs, on the other hand, they also have the right to collect taxes. for funding, as well as imposing penalties as regulatory enforcement sanctions. The data analysis technique used is a qualitative analysis technique. The results of this analysis show that in Indonesia, there are various types of public organizations that have different roles and functions in government and society, such as government institutions to BUMN, BUMD, community organizations, NGOs and international organizations. These various public organizations have an important role in development and governance in Indonesia, and play different roles in supporting the various needs of society and the state.